Da’wah management in halal tourism development: Implementing Pentahelix Synergy and the ACES 3.0 framework - Irsyad, Mohamad; Mursyid, Achmad Yafik (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose – This research aims to explore strategies using the criteria used in the Global Muslim Travel Index 2023, namely the ACES 3.0 framework with pentahelix synergy.Method – This research uses a qualitative method. Data collection techniques were carried out using two processes: literature review and documentation review.Results – This study shows that the Access and Environment criteria need much attention from stakeholders. The recommended suggestion is to increase collaboration between parties. While the implementation of communication and service criteria has been going quite well, it still requires the attention of stakeholders, especially regarding the provision of halal food.Implications – This research suggests further improving stakeholder collaboration to develop halal tourism to increase state revenues that can contribute to Indonesia's economic development.Originality/Value – Research on pentahelix synergy within the ACES 3.0 Framework reveals a novel approach where academia, business, government, community, and media collaborate to foster sustainable innovation and resilience. This collaborative model leverages interdisciplinary strengths to address complex societal challenges, enhancing the impact and reach of each stakeholder’s contribution.***Tujuan – Penelitian ini bertujuan untuk mengeksplorasi strategi menggunakan kriteria yang digunakan dalam Indeks Perjalanan Muslim Global 2023, yaitu kerangka ACES 3.0 dengan sinergi pentahelix.Metode – Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data dilakukan dengan dua proses: tinjauan literatur dan tinjauan dokumentasi.Hasil – Studi ini menunjukkan bahwa kriteria Akses dan Lingkungan memerlukan perhatian yang besar dari para pemangku kepentingan. Saran yang direkomendasikan adalah meningkatkan kerja sama antara pihak-pihak. Sementara implementasi kriteria komunikasi dan pelayanan telah berjalan cukup baik, namun masih memerlukan perhatian dari para pemangku kepentingan, terutama mengenai penyediaan makanan halal.Implikasi – Penelitian ini menyarankan untuk meningkatkan kerja sama pemangku kepentingan untuk mengembangkan pariwisata halal guna meningkatkan pendapatan negara yang dapat berkontribusi pada pengembangan ekonomi Indonesia.Originalitas/Nilai – Penelitian tentang sinergi pentahelix dalam Kerangka ACES 3.0 mengungkap pendekatan baru di mana akademisi, bisnis, pemerintah, masyarakat, dan media bekerja sama untuk mendorong inovasi dan ketahanan yang berkelanjutan. Model kolaboratif ini memanfaatkan kekuatan lintas disiplin untuk mengatasi tantangan-tantangan sosial yang kompleks, meningkatkan dampak dan jangkauan kontribusi masing-masing pemangku kepentingan.